Investigating the association of atopic dermatitis with ischemic stroke and coronary heart disease: A mendelian randomization study - Huang, Jian; Gui, Ying; Wu, Jing; Xie, Yubo (Frontiers in Genetics, 2022)
Background: Atopic dermatitis (AD) is the most common chronic skin inflammatory disease. Prior observational studies have reported inconsistent results on the association of AD with ischemic stroke and coronary heart disease. In this study, we applied two-sample Mendelian randomization (MR) to evaluate the causal effect of AD on ischemic stroke and coronary heart disease. Methods: Twelve single nucleotide polymorphisms robustly associated with AD (P < 5 × 10−8) were obtained from a genome-wide association study including 10788 cases and 30047 controls by the EArly Genetics and Life course Epidemiology (EAGLE) Consortium (excluding the 23andMe study). The corresponding data for ischemic stroke (34217 cases and 406111 controls), large artery stroke (4373 cases and 406111 controls), cardioembolic stroke (7193 cases and 406111 controls), small vessel stroke (5386 cases and 192662 controls), coronary heart disease (122733 cases and 424528 controls), and myocardial infarction (43676 cases and 128199 controls) were obtained from the MR-Base platform. In the primary MR analyses, we applied the inverse variance weighted method to evaluate the associations. We performed sensitivity analysis using the weighted median, MR-Egger, weighted mode, simple mode, MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO), and leave-one-out methods. Results: In the primary MR analyses, we found no causal association of genetically predicted AD with all ischemic stroke (odds ratio [OR]=1.00, 95% confidence interval [CI]: 0.95-1.06), large artery stroke (OR=1.02, 95% CI: 0.88-1.17), cardioembolic stroke (OR=1.06, 95% CI: 0.94-1.18), small vessel stroke (OR=1.05, 95% CI: 0.94-1.17), coronary heart disease (OR=1.00, 95% CI: 0.94-1.05), and myocardial infarction (OR=1.03, 95% CI: 0.98-1.09). The results from the primary MR analyses were supported in sensitivity analyses using the weighted median, weighted mode, simple mode, and MR-Egger methods and multivariable MR analyses adjusting for asthma and several traditional risk factors for ischemic stroke and coronary heart disease. MR-Egger intercepts provided no evidence of directional pleiotropy. The MR-PRESSO and leave-one-out analyses did not indicate any outlier instruments. Conclusion: Our MR study does not support a causal association of genetically predicted AD with all ischemic stroke, large artery stroke, cardioembolic stroke, small vessel stroke, coronary heart disease, and myocardial infarction.